Analisis Strategi Penerjemahan Dalam Film â€œThe Spy Next Doorâ€ - Didi Hermawan (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The Spy Next Door is one of family movie where Jacky Chan plays in the movie. This paperÂ aims to study about what strategies of translating which exists and is applied ny translator in subtitiling or translating in The Spy Next Door movie. In this mini research, the researcher found that the meaning of word or sentence depends on the context, either situational context or cultural context. It is clear that American culture is different with Indonesianâ€™s. The translation shows that â€œHalloweenâ€ cannot be translated â€œSuronanâ€. They are different each other. There is no â€œHalloweenâ€ in Indonesian culture. The researcher found that the strategies used in The Spy Next Door movie are Expansion, paraphrase, transfer, Imitation, condensation, deletion, and resignation.